PERAN WAKAF DALAM PEREKONOMIAN (STUDI WAKAF TUNAI TERHADAP PEMBANGUNAN EKONOMI) - Abdul Rahman Hidayat (Perisai : Islamic Banking and Finance Journal, 2016)
Waqf is an instrument for the welfare of the people who first performed by Umar ibn Al Khatthab permission of the Prophet. At that time, Umar had a garden plot of fertile and productive in Khaibar dei to there is a passion for helping others and for the welfare of the people, then Umar bin al Khatthab consult to the Prophet. How you can donate the garden ?. The Prophet suggested that the estate remains substantially and well run and the results are donated to the community. That is, just to be maintained and managed, while the results are donated for the benefit of the people. Similarly, when the bi Ali Abi Talib and Uthman bin Affan donated part of his fortune to be managed and the results are donated for the benefit of society.